Can Capital Ratios be the Centre of Banking Regulation – A Case Study - Milena Marinova (European Financial and Accounting Journal, 2009)
The application, or to be more precise, the misapplication of securitization in the mortgage market had fatal consequences for the financial sector worldwide. More over securitization techniques enabled single banks to reduce their individual risk while at the same time transferred greater risk to the financial system. Meanwhile a lot was written on the causes for the recent financial crisis. In most cases inadequate ratings provided by the credit rating agencies and different principal agency problems were addressed. I argue that international and national financial supervisors established an inadequate framework for financial regulation and supervision, and among other failures, even supported credit rating agencies to further establish their businesses. Further on, I argue that early warning indicators of systemic risk in the financial sector and signs of the coming turmoil were irresponsibly ignored at the time they were perceived. What turned obvious during and after the recent financial turmoil is that capital regulation failed to reach its main goal – ensuring stability of the financial system. In particular, securitization and related credit risk transfer products were adequately treated neither in Basel I nor in Basel II. With the development of both Basel Accords capital ratios became the center of banking regulation. However, capital ratios are obviously not sufficient as a measure for a systemic financial stability. It is time to ask if the developments in Basel II are the right way of banking regulation and supervision and in particular, if capital ratios can be the centre of banking regulation?
Keywords: G2; G21; G24; G28; 650; Mortgage securitization; Financial crisis; Banking regulation; Capital adequacy